Austerity measures amplified crisis in Spain, Portugal, and Italy - Philipp Engler; Mathias Klein (DIW Economic Bulletin, 2017)
The fiscal consolidation efforts of Spain, Italy, and Portugal from 2010 to 2014 did not achieve their goal of reducing the debt-to-GDP ratio in any of the three countries. This Economic Bulletin examines why the spending cuts and tax increases, at times drastic, were unsuccessful and perceptibly contributed to sending the three countries back into recession. The sharp decrease in private household debt played a key role, especially in Spain. It weakened private consumption, and subsequent reductions in public spending amplified the slowdown with negative consequences on growth and tax revenues. The austerity policy also appears to have had a negative impact on productivity, neutralizing the beneficial effects of structural reforms. Contrary to widespread opinion, the lack of structural reforms was not the key reason for the austerity policy's failure. The goal of reducing the debt-to-GDP ratio can only be achieved with a balanced policy mix of structural reforms, mild austerity measures, and if possible, budget reallocation in favor of investment.
Keywords: E24; E32; E44; E62; 330; fiscal consolidation; private debt; hysteresis